The influence of digital marketing, brand image and product quality on product purchasing decisions at the King MS Glow shop in the city of Bengkulu / Ghaefira Nur Fatimah, Islamuddin Islamuddin and Meilaty Finthariasari - Nur Fatimah, Ghaefira; Islamuddin, Islamuddin; Finthariasari, Meilaty (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study aims to explain the influence simultaneously (together) or partially between the influence of Digital marketing, brand image and product quality on purchasing decisions. This study uses a quantitative approach with survey research, and use 110 consumers respondents of King MS Glow Bengkulu City as sample. The data collection method used is the distribution of questionnaires and then it processed on SPSS 26 Version. The results of this study indicate that partially Digital Marketing have a positive effect, brand image and product quality have a positive and significant effect on purchasing decisions for King MS Glow Bengkulu. Meanwhile, simultaneously the results of this study also show that social media marketing, brand image and product quality have a positive and significant effect on purchasing decisions for King MS Glow Bengkulu products.